THE INFLUENCE OF BREAST CANCER EDUCATION ON INTEREST IN BREAST SELF-EXAMINATION (BREAST SELF-EXAMINATION) IN ADOLESCENTS AT AL-AMANAH VOCATIONAL SCHOOL, TANGERANG YEAR 2023 - Mandasari, Yunita; Futtriani, Elfira Sri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Breast cancer, also known as mammary carcinoma, is a form of cancer that can affect anyone, both women and men. This disease develops in the mammary glands, fatty tissue, or in the connective tissue of the breast. Research Objective: To find out whether there is an impact of breast cancer education on teenagers' interest in doing BSE?. Research Method: This study uses an experimental method with a quasi-experimental type (Quasi Experiment) using a Pre-Test Post-Test design approach. Research Results: Based on the results of the research, it shows that there is an influence of breast cancer education on interest in BSE, the value of which is 6,517 and the p value = 0.000 < alpha 0.05 so that H0 is rejected and Ha is accepted, indicating that there is an impact of breast cancer education on interest in self-examination of the breasts. at SMK AL Amanah Tanggerang in 2023. Conclusions and suggestions: There is an influence of breast cancer education on interest in doing BSE after conducting Pre-Test Post-Test research nd it is hoped that future researchers will carry out deeper research on breast cancer education and interest in carrying out BSE.